Jack : the early years of John F. Kennedy - Cooper, Ilene (New York : Dutton Children's Books, 2003)
A description of the childhood and youth of John Fitzgerald Kennedy, the thirty-fifth president of the United States.
Includes bibliographical references and index.
HB 03/03, SJ 02/03, BC 02/03, PW 12/16/02, KK 12/15/02
1014
Keywords: Kennedy, John F. -- 1917-1963 -- Childhood and youth -- Juvenile literature; Kennedy, John F. -- 1917-1963 -- Childhood and youth; Presidents -- United States -- Biography -- Juvenile literature; Presidents